Activation of orexin-A (hypocretin-1) receptors in the Raphe Pallidus at different ambient temperatures in the rat: effects on thermoregulation, cardiovascular control, sleep, and feeding behavior - Hitrec, Timna; Del Vecchio, Flavia; Alberti, Luca; Luppi, Marco; Martelli, Davide; Occhinegro, Alessandra; Piscitiello, Emiliana; Taddei, Ludovico; Tupone, Domenico; Amici, Roberto; Cerri, Matteo (Frontiers in Neuroscience, 2024)
The Raphe Pallidus (RPa) is a brainstem nucleus containing sympathetic premotor neurons that control thermogenesis and modulate cardiovascular function. It receives inputs from various hypothalamic areas, including the Lateral Hypothalamus (LH), a heterogeneous region intricately involved in several autonomic and behavioral functions. A key subpopulation of neurons in the LH expresses orexin/hypocretin, a neuropeptide which is crucially involved in the regulation of the wake–sleep states and feeding behavior. The RPa receives orexinergic projections from the LH and orexinergic signalling in the RPa has been shown to enhance thermogenesis in the anaesthetized rat, but only in the presence of an already existing thermogenic drive, without significantly affecting cardiovascular function. The present work was aimed at exploring the effects on thermoregulation and autonomic function and the possible role in the modulation of the wake–sleep states and feeding behavior of orexin injection in the RPa in the free-behaving rat. In order to assess the influence of an already present thermogenic drive on orexinergic signalling in the RPa, animals were studied at three different ambient temperatures (Ta, 10°C, 24°C, and 32°C). We found that orexin injection into the RPa variably affected the wake–sleep states, autonomic functions, motor activity, and feeding behavior, at the different Tas. In particular, in the first post-injection hour, we observed an increase in wakefulness, which was large at Ta 24°C and Ta 10°C and rather mild at Ta 32°C. Deep brain temperature was increased by orexin injection at Ta 10°C, but not at either Ta 24°C or Ta 32°C. Moreover, an increase in mean arterial blood pressure occurred at Ta 24°C, which was probably masked by the high baseline levels at Ta 10°C and was completely absent at Ta 32°C. Finally, an enhancement in feeding behavior was observed at Ta 24°C and 10°C only. In accordance with what observed in anaesthetized rats, orexinergic signalling in the RPa seems to be ineffective in the absence of any thermogenic drive. Moreover, the effects observed on the wake–sleep states and feeding behavior introduce the RPa as a novel player in the central neural network promoting wakefulness and feeding.